Antigen binding molecules : antibodies and T-cell receptors - Haber, Edgar, 1932-1997 (Advances in protein chemistry, 1996)
Topics Covered Include:. X-ray crystallography of ligands. Catalytic antibodies. Nature of the antigen. Antibody binding sites. Maturation of the immune response. Computational biochemistry of antibodies and T-cell receptors. Antigen-specific T-cell recep.